(3GdCQHYhf GdfhhjI ef cdGe NjQ GdHQjIs - (3GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjGA, eMj GdOjf, jMj Hf TQa Hf eQj, J (B676(3g`s ((3CMeO GdShjaj GdhGUdj GdeGdcj GdCRgQjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf h HYO abO QhjfG Yf Ydj Hf CHj WGdH hYHO Gddg Hf eSYhO heYGP Hf LHd hCHj GdOQOGA hGHf YeQ hGHf YHGSs
(3BNQgG (B:s
(3Ke dbjJfj dG JTQc Hj TjFG dCJjJc HbQGHgG eZaQI QhGg GdJQePj hbGd MOjK MSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 149s
(3eYLe GdeDdajf (B4 / 98s
(3cTa GdXfhf (B1 / 59s
(3TPQGJ GdPgH (B5 / 354 - 356s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs